PEMANFAATAN LIMBAH POPOK SEBAGAI SARANA PENDIDIKAN KARAKTER PEDULI LINGKUNGAN ANAK USIA DINI - Talitha Widiatningrum; Krispinus Pukan; R Susanti; Sri Sukaesih (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2018)
TK Wiji is a nursery school which was built at Jl. Untung Suropati no. 10 kelurahan Tegalrejo kota Pekalongan based on NPSN 69879295 of 2005 by Yayasan 99. TK Wiji is growing fast due to its education system which is in line to the 2013 national curriculum with the vision of toodler characteristic development. The most fundamental of character education is environment education. Considering to this situation, we have found that the most common litter of the nursery is disposable diaper. This kind of diaper is hardly degraded into its monomer. Colon’s research in 2013 has found a strategy to use this diaper as compost. Based on the problem of disposable diaper wastes in the nursery and also the result of the background research about exploiting the waste as compost, then the environment education for toodler of TK Wiji by using diaper waste as a material for hidroponic cultivation was done. In the beginning, guidances were given to the teacher in 2 phases which are making diaper waste composite into organic fertilizer and making hidrogel for interior plant cultivation by using the gel of the waste. In the next step, the teachers were asked to make improvisation regarding toodler environment education by using the skills. In spite of this, there was still an argument about the time management in the learning process by using diaper waste as the material. Thus an implementation of the skill for toodler extracuricular was stated.